2014
DOI: 10.1016/j.drugalcdep.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Pilot randomized controlled trial of an internet-based smoking cessation intervention for pregnant smokers (‘MumsQuit’)

Abstract: BackgroundInternet-based Smoking Cessation Interventions could help pregnant women quit smoking, especially those who do not wish to, or cannot, access face-to-face or telephone support. This study aimed to preliminarily evaluate the effectiveness and usage of a fully automated smoking cessation website targeted to pregnancy, ‘MumsQuit’, and obtain an initial effect-size estimate for a full scale trial.MethodsWe recruited 200 UK-based pregnant adult smokers online to a two-arm double-blind pilot RCT assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 42 publications
(38 reference statements)
2
56
0
Order By: Relevance
“…Three studies used videotapes (Cinciripini et al, 2000;Price et al, 1991;Secker-Walker et al, 1997), and one study used telephone Interactive Voice Response Technology (IVR) (Ershoff et al, 1999). Two trials used websites, including a contingency management programme (Harris & Reynolds, 2015), and an interactive and personalised website, 'MumsQuit' (Herbec, Brown, Tombor, Michie, & West, 2014). The remaining two trials were computer programmes.…”
Section: Digital Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies used videotapes (Cinciripini et al, 2000;Price et al, 1991;Secker-Walker et al, 1997), and one study used telephone Interactive Voice Response Technology (IVR) (Ershoff et al, 1999). Two trials used websites, including a contingency management programme (Harris & Reynolds, 2015), and an interactive and personalised website, 'MumsQuit' (Herbec, Brown, Tombor, Michie, & West, 2014). The remaining two trials were computer programmes.…”
Section: Digital Interventionsmentioning
confidence: 99%
“…Five control arms used usual care, which was described as standard physician, obstetrician or nurse-midwife/midwife advice (Lawrence et al, 2003;Naughton et al, 2017;Ondersma et al, 2012;Price et al, 1991;Secker-Walker et al, 1997). Three trials used digitalised interventions as the comparator group: text-message comparison groups (Abroms et al, 2017;Pollak et al, 2013) and a static website providing brief smoking cessation advice (Herbec et al, 2014). One intervention used a nurse-led telephone counselling system (Harris & Reynolds, 2015).…”
Section: Comparator Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Others are based on financial incentives [8][9][10] and nicotine replacement therapy. [11][12][13] While some of these interventions have improved cessation during pregnancy, they lack effectiveness for the prevention of postpartum relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few digital smoking cessation interventions have been designed specifically for pregnant smokers, but both Web sites and text-messaging programmes [1518] have been found to be acceptable and potentially engaging in this population, and pilot comparative trials have shown positive but not statistically significant effects of these interventions [1921]. However, to the best of our knowledge, no study has been published on the development or evaluation of smoking cessation apps for pregnant smokers.…”
Section: Introductionmentioning
confidence: 99%